2003
DOI: 10.1002/bdrb.10006
|View full text |Cite
|
Sign up to set email alerts
|

Rat embryos express transcripts for cyclooxygenase‐1 and carbonic anhydrase‐4, but not for cyclooxygenase‐2, during organogenesis

Abstract: BACKGROUND: Acetylsalicylic acid (ASA) is a rat teratogen, and exposures on gestational days (GDs) 9 and 10 induce diaphragm, cardiac, and midline defects. ASA inhibits members of the cyclooxygenase (COX) family and potentially members of the carbonic anhydrase (CA) family. The objective of this study was to determine whether the mRNA developmental expression pattern for any COX or CA isoform was consistent with a model in which ASA teratogenicity is mediated through direct interaction with one of these enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
0
18
0
1
Order By: Relevance
“…This finding suggested that the developmental toxicity is mediated by COX-1 or COX-2 inhibition, where irreversible inhibition produces a greater developmental toxicity signal. Subsequent to this review, two studies strengthened the conclusion that COX-1 mediates these developmental signals (Cappon et al, 2003a;Streck et al, 2003). Cappon et al (2003a) selected a series of NSAIDs with different capacities to inhibit COX-1 and COX-2 and administered them to pregnant rats and rabbits during the sensitive period for heart development and midline closure.…”
Section: Mousementioning
confidence: 97%
See 2 more Smart Citations
“…This finding suggested that the developmental toxicity is mediated by COX-1 or COX-2 inhibition, where irreversible inhibition produces a greater developmental toxicity signal. Subsequent to this review, two studies strengthened the conclusion that COX-1 mediates these developmental signals (Cappon et al, 2003a;Streck et al, 2003). Cappon et al (2003a) selected a series of NSAIDs with different capacities to inhibit COX-1 and COX-2 and administered them to pregnant rats and rabbits during the sensitive period for heart development and midline closure.…”
Section: Mousementioning
confidence: 97%
“…Hence, studies conducted well below the MTD and those conducted with doses exceeding the MTD may be unable to detect low-incidence developmentally toxic effects of NSAIDs. The potential association of NSAIDs with developmental toxicity, as shown by the literature, and the limitations of this data set, as discussed above, led to us to reinvestigate the developmental toxicity of aspirin in rats and rabbits in a series of studies by using two different dosing paradigms (Cappon et al, 2003b;Gupta et al, 2003), to assess the developmental toxicity of NSAIDs with different COX-1 and COX-2 specificities (Cappon et al, 2003a), and to examine the expression of COX-1 and COX-2 in developing rat embryos (Streck et al, 2003). Concurrent with these studies, a metaanalysis of the human epidemiologic data was conducted examining the use of aspirin during pregnancy by analyzing first-trimester outcomes (Kozer et al, 2002) and second-and third-trimester outcomes (Kozer et al, 2003).…”
Section: Mousementioning
confidence: 99%
See 1 more Smart Citation
“…Carnovale et al (2001) reported that aspirin could inhibit prostaglandin in a dose-dependent manner, which is the main prostaglandin involved in cultivation and decidualization, cytokine production, and ovulation. In addition, aspirin induces embryo teratogenicity (Streck et al, 2003), drawing attention to its toxicity. Kozer et al (2002) conducted a meta-analysis showing that aspirin exposure during the first trimester may be associated with an increased risk of gastroschisis.…”
Section: Discussionmentioning
confidence: 99%
“…Обе изоформы ЦОГ имеют разные уровни экспрессии. Так, у эмбрионов крыс на про-тяжении органогенеза обнаруживается только мРНК ЦОГ-1 [76]. Отмечается, что нежелательные побочные реакции неселективных НПВП связаны главным образом с ингибированием ЦОГ-1.…”
Section: обзор литературыunclassified